2014
DOI: 10.1075/intp.16.2.03che
|View full text |Cite
|
Sign up to set email alerts
|

The use of reported speech and the perceived neutrality of court interpreters

Abstract: A mock trial, with two-way consecutive interpreting between Cantonese and English, was used to test perceptions of a court interpreter’s neutrality when interpreting into Cantonese in reported rather than direct speech. Monolingual Cantonese speakers played the part of witnesses using the interpreter. Three groups were created: a control group (16 participants), receiving interpretation of all English utterances into Cantonese in direct speech; and two experimental groups (17 participants each). The experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…This short opinion article is intended as a position paper for general readers. There have been several studies on question types (Liu, 2020), reported speech (Cheung, 2012(Cheung, , 2014(Cheung, , 2017(Cheung, , 2018 and speech style features (Lee, 2009(Lee, , 2011 and the implications for procedural fairness and judicial outcomes in interpreter-mediated courtroom interactions. However, little has been explored about the concept of the Manner of Speech.…”
Section: Discussionmentioning
confidence: 99%
“…This short opinion article is intended as a position paper for general readers. There have been several studies on question types (Liu, 2020), reported speech (Cheung, 2012(Cheung, , 2014(Cheung, , 2017(Cheung, , 2018 and speech style features (Lee, 2009(Lee, , 2011 and the implications for procedural fairness and judicial outcomes in interpreter-mediated courtroom interactions. However, little has been explored about the concept of the Manner of Speech.…”
Section: Discussionmentioning
confidence: 99%
“…The study of reported speech, and the identity role assignment it explicates, gained momentum in court interpreting (since it is important to be able to assign agency before assigning blame). Cheung (2012) and Cheung (2014) are examples of studies focusing on pronoun choices of court interpreters in Hong Kong. However, agency and participant roles can come into play in other domains as well, for instance, political meetings (Zhan, 2012) or international conferences on such disparate subjects as publishing and floral art (Chang & Wu, 2009).…”
Section: Participation Frameworkmentioning
confidence: 99%
“…This also increased the demand for concentration by the interpreter, who not only needed to focus on the message but also on the surroundings where the media was taking place in a different location from the interpreter. Under such circumstances, there were occasions where the interpreters resorted to indirect speech, which inevitably influenced the audience perception of the interpreter as being aligned or otherwise with one or more of the interlocutors as they were switching very quickly on the screen (Cheung, 2018(Cheung, , 2014b.…”
Section: Paralinguistic Demandsmentioning
confidence: 99%